2013
DOI: 10.1007/s10903-013-9832-6
|View full text |Cite
|
Sign up to set email alerts
|

Labour Exploitation and Health: A Case Series of Men and Women Seeking Post-Trafficking Services

Abstract: Research on the health of trafficked men and on the health problems associated with trafficking for labor exploitation are extremely limited. This study analysed data from a case series of anonymised case records of a consecutive sample of 35 men and women who had been trafficked for labor exploitation in the UK and who were receiving support from a non-governmental service between June 2009 and July 2010. Over three-quarters of our sample was male (77 %) and two-thirds aged between 18 and 35 years (mean 32.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
105
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 19 publications
2
105
0
2
Order By: Relevance
“…51 Of these, only 12 included forms of trafficking beyond sexual exploitation, and none of the latter targeted the child population. In many studies on human trafficking, researchers have included aggregate results for adults and children, 68 -70 boys and girls, 30 or individuals from multiple countries of origin. 71,72 Some researchers also combine victims of differing forms of trafficking.…”
Section: Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…51 Of these, only 12 included forms of trafficking beyond sexual exploitation, and none of the latter targeted the child population. In many studies on human trafficking, researchers have included aggregate results for adults and children, 68 -70 boys and girls, 30 or individuals from multiple countries of origin. 71,72 Some researchers also combine victims of differing forms of trafficking.…”
Section: Researchmentioning
confidence: 99%
“…28 Of note, researchers in other studies have shown a predominance of boys in labor trafficking, suggesting that there may be regional differences among trafficking victims or a failure to recognize male victims in the United States. 29,30 Factors at the individual, family, community, and societal levels contribute to human trafficking vulnerability in the United States and around the globe (Table 2). Children and youth who identify as lesbian, gay, bisexual, transgender, or queer (LGBTQ); those who are American Indian girls; and boys and girls with a history of abuse or neglect, substance misuse, or homelessness may constitute a significant proportion of trafficked youth.…”
mentioning
confidence: 99%
“…[3][4][5] High levels of physical and mental health problems have been reported among victims of human trafficking, including non-specific symptoms such as headache, back pain, stomach pain and dizziness, and mental disorders such as depression, anxiety and post-traumatic stress disorder. [6][7][8] However, little is known about the extent to which healthcare professionals come into contact with victims of trafficking, or about their knowledge and readiness to identify victims, to make appropriate referrals, and to provide clinical care.…”
Section: Introductionmentioning
confidence: 99%
“…The global number of trafficked persons at any time is estimated to be 2.5 million [2]. Trafficked women and men are commonly exposed to severe trauma characterised by physical and sexual violence and threats while trafficked [5-9], and among those trafficked for sexual exploitation there is a high risk of HIV infection [8,10-12]. Evidence on the nature of psychological disorders among survivors of human trafficking is, however, very limited [8].…”
Section: Introductionmentioning
confidence: 99%